GUIDELINES FOR PROMOTING SUCCESS IN THE OPERATIONS OF COMMUNITY ENTREPRENEURS IN THE WESTERN REGION - Pongsittikanchana, Chantana; Pongsittikanchana, Thongchai (RMUTT Global Business and Economics Review, 2021)
The purpose of this research was to examine factors affecting success in operations and guidelines to promote success in operations of community entrepreneurs in the western region.Samples recruited by stratified sampling included 200 community enterprise entrepreneurs and OTOP entrepreneurs, and 5 key informants. Research instrumentation had 2 parts comprising questionnaire and question guidelines for in-depth interview. Data analysis methods took on descriptive statistics, multiple regression analysis, and content analysis. Research findings are as follow. 1. Factors affecting success in operations of community entrepreneurs in the western region at a significant level of .01 were management factor (β=.429), innovations factor (β=.364), and network factor (β=.187) and could predict 89.9 percent (R2= .899) of success in operations of community entrepreneurs in the western region. Leadership factor and community organization factor insignificantly affected success in operations. 2. Guidelines for promoting success in operations involve leadership factor by changing operational concept; community organization factor by promoting participation; management factor by applying business management approach; innovations factor by adopting community wisdom; and network factor by coordinating with external agencies.